Variability Of Some Selection Parameters of Karakol Sheep in the Conditions of the Sandy Desert - Gaziev Adxam; Mamatov Baxtiyor Salimovich (Zien Journals, 2022)
The article describes the results of the study of the variation of some selection parameters of black Karakol sheep depending on the mating types.
Keywords: Karakol ewes; lambs; mating; length